2015
DOI: 10.1111/pcmr.12378
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory pathways regulate expression of a spliced FKBP51 isoform in lymphocytes of melanoma patients

Abstract: FKBP51 (gene FKBP5) is an immunophilin capable of immunosuppression expressed in melanoma and lymphocytes. We found increased levels of a spliced FKBP5 variant in the PBMCs of 124 patients with melanoma. This variant encodes for an unknown isoform (FKBP51s). We hypothesized that FKBP51s resulted from tumour interaction with immune cells, through PDL-1/PD-1. To address this issue, we performed melanoma/PBMC cocultures. Furthermore, the immunohistochemistry of 76 melanoma specimens served to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…As shown in Figure 1A , both the canonical and the spliced FKBP51 isoforms were expressed in the glioblastoma cells. Whereas in melanoma, FKBP51s was barely detected under basal conditions [ 16 ]. FKBP51s expression in glioblastoma cells was confirmed by fluorescent microscopy (Figure 1B ), showing a localization in both nuclear and cytoplasmic compartments (Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 1A , both the canonical and the spliced FKBP51 isoforms were expressed in the glioblastoma cells. Whereas in melanoma, FKBP51s was barely detected under basal conditions [ 16 ]. FKBP51s expression in glioblastoma cells was confirmed by fluorescent microscopy (Figure 1B ), showing a localization in both nuclear and cytoplasmic compartments (Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…The targeting of mechanisms that control post-translational modification can help in neutralizing the pro-tumoral effect of PD-L1. Our research has previously identified a role for a spliced variant of the FKBP5 gene in the regulation of PD-L1 expression in melanoma [ 16 ]. FKBP5 encodes a large immunophilin which was originally cloned in lymphocytes [ 17 ] but also found abundantly expressed in several tumours [ 18 23 ], including glioblastoma [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Gene expression was performed using the SsoAdvancedTM SYBR Green Supermix (Bio-Rad, Hercules, CA, USA), and specific qPCR primers to analyse each transcript, particularly, to detect FKBP51, X-linked inhibitor of apoptosis protein (XIAP) and BCL-2 validated QuantiTec primers from Qiagen (Valencia, CA, USA) were used, along with co-amplified ribosomal 18S and b-Actin as internal controls for normalization. 28,48 For the comparison between thymus, skin cases and MF groups, quantitative gene expression for FKBP51 was performed with the 2 ÀDCT comparative method. Quantitative gene expression for FKBP51, XIAP and BCL-2 in MF cases was performed as relative expression change fold using normal thymus as reference sample.…”
Section: Histochemistrymentioning
confidence: 99%